An improved CARI algorithm based on sliding window in MIMO-OFDM system - Zhang Hui; Xia Liling; Dong Rongwei; Wang Huihui (КНУБА, 2018)
MIMO-OFDM is one of the core technologies in mobile communication system. As multicarrier modulation is adopted, the MIMO-OFDM system usually leads to high Peak-To-Average power ratio (PAPR), which can decrease the communication quality. The cross-antenna rotation and inversion (CARI) is an algorithm with better performance to reduce Peak-To-Average power ratio of MIMO-OFDM system. However, needing a large number of iterations is a shortage of CARI. The sub-optimal scheme of CARI – successive suboptimal CARI (SS-CARI) can reduce the number of iterations, but the PAPR reducing performance of it is lost largely. In view of this problem, a sub-optimal CARI method using sliding window to search for rotation and reverse combination is proposed in this paper. By using sliding window to search for the local optimal rotation and reverse combination, not only the overall traversal search can be avoided and the computational complexity of CARI algorithm can be reduced greatly, but also the PAPR reduction performance of SS-CARI can be improved. Simulation results show that a good trade-off between complexity of system and the PAPR reduction performance can be achieved by applying the proposed scheme.
Keywords: peak to average power ratio (PAPR); MIMO-OFDM systems; cross-antenna rotation and inversion (CARI); sliding window; 621.396.23